DETERMINAN ANGKA HARAPAN HIDUP 34 PROVINSI DI INDONESIA (ANALISIS DATA PANEL) - Muhammad Ryan Mahendra; Syamsurijal Tan; Yohanes Vyn Amzar (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effect of per capita income, average years of schooling, and poverty rate on life expectancy in the regencies and cities of Jambi Province. The study uses secondary data obtained from the Central Bureau of Statistics (BPS) and applies panel data regression analysis covering 11 regencies/cities during the period 2010–2023. The results show that per capita income and average years of schooling have a positive effect on life expectancy, while the poverty rate has a negative effect on life expectancy. These findings indicate that improvements in economic welfare and education can enhance the quality of life and increase life expectancy, whereas higher levels of poverty may reduce the overall health condition of the population. Therefore, development policies that focus on increasing income, expanding equal access to education, and reducing poverty are needed to improve life expectancy in Jambi Province.